Raised Shoreline Phenomena and Postglacial Emergence in South-Central Newfoundland - Tucker, C.; Leckie, D.; McCann, S. (Géographie physique et Quaternaire, 1982)
ABSTRACTTwo types of raised marine shoreline features occur in the Burin-Hermitage area of southern Newfoundland marine benches cut in bedrock, and terraces and beaches developed in unconsolidated materials. Most of the benches are older than Late Wisconsinan, and a horizontal rock shoreline at 4.5 ± 1.5 m, which occurs throughout the region, was probably formed in the last interglacial period. Raised deltas and coastal outwash deposits graded to former sea level positions, which define the Late Wisconsinan marine limit across the northern part of the study area, are correlated with terraces and raised beaches further south on the Burin Peninsula. The elevations of these features are used to define the regional pattern of postglacial emergence. More than 30 m of emergence has occurred in the northwest, but the extreme southern part of the region is undergoing submergence.